Estudo da purificação do àcido clavulânico utilizando processo contínuo de adsorsão - Almeida, Renata Maria Rosas Garcia (2003)
Clavulanic acid (CA), a beta-lactam antibiotic, has been known for its commercial and therapeutic importance. This antibiotic is produced by an actinomicete, Streptomyces clavuligerus, and has a combined use with penicillins, acting as inhibitor of beta-lactamase enzymes. Due this importance, some studies on clavulanic acid production has been developed at DEQ-UFSCar. As a natural consequence of these studies and the global knowledge of this process it was necessary to develop a work studying clavulanic acid purification. The adsorption process was chosen to be studied as the process of clavulanic acid recovery and purification. In the present work a continuous adsorption process for clavulanic acid purification was proposed. This process utilized two stirred tanks (CSTR) with recycle of the adsorbent material. The adsorbent chosen to this process was the ion exchange resin Amberlite IRA 400 in the chloride cycle. First, it was necessary to study the adsorption and desorption kinetics and the clavulanic acid equilibrium isotherms in that resin to investigate the influence of temperature, pH and clavulanic acid initial concentration. The degradation rate of clavulanic acid in basic and acidic solutions is very high; high temperatures also increase the degradation rate. Consequently, studies on clavulanic acid degradation were carried out in the same temperature and pH conditions of the kinetics studies. A mathematical model was proposed to describe the adsorption and desorption processes and the kinetics and transport parameters were determined. The continuous process was also mathematically modeled to obtain preliminary data to carry out the clavulanic acid continuous experiments. The parameters utilized in the continuous adsorption process were optimized by response surface analysis to maximize yield and concentration and purification factors. Experiments of the continuous adsorption process were carried out in some different conditions. The continuous process like proposed was operationally viable, but the concentration and purification factors obtained were lesser than those obtained in fixedbed experiments.